Teaching cultural humility for social workers serving LGBTQI Aboriginal communities in Australia. Issue 5 (4th July 2019) - Bennett, Bindi; Gates, Trevor G.
ABSTRACT: It is well documented that colonization and subsequent repressive policies have wrought devastating changes in the lives of Aboriginal people in Australia. Social workers are an essential group for improving social justice and self-determination for Australian Aboriginal people. The Australian Association of Social Workers (AASW) acknowledges that Aboriginal people make a unique contribution to the life of the nation and mandates that social work educational programs provide culturally responsive content that acknowledges the value and contributions of Aboriginal people. Social work educators need to embed this content without reinforcing stereotypes or being tokenistic. This is a challenge when teaching about intersecting identities, such as lesbian, gay, bisexual, transgender, queer/questioning, and intersex (LGBTQI) Aboriginal people. We outline the terms used in this space and propose that cultural humility is an acceptable framework to consider. We introduce key conceptual terms used in LGBTQI Aboriginal communities. Finally, we provide recommendations for engaging with LGBTQI Aboriginal peoples.